Identifikasi Disfemisme pada Siniar “Siaran Darurat Comikaze” dalam Kanal YouTube Comika - Rini Dwi Cahyati; Julisah Izar; Anggi Triandana (MAN 4 Kota Pekanbaru, 2026)
This study aims to identify the types and functions of dysphemism in the podcast “Siaran Darurat Comikaze” on the Comika YouTube channel. Dysphemism is understood as the use of words or expressions that are coarse, rude, or that intensify the meaning of words that are otherwise neutral, for a specific purpose. This study employs a qualitative descriptive method, utilizing the note-taking technique to collect data from the transcripts of episodes 1 through 13 during the period from April to September 2025. The results identified 281 instances of dysphemism categorized into seven types: taboo terms 26 instances, curses or profanity 67 instances, comparisons of humans to animals associated with specific behaviors 58 instances, nicknames based on physical characteristics 3 instances, nicknames based on mental abnormalities 60 instances, -ist dysphemisms 14 instances, and insulting terms targeting the subject’s character 39 instances. Additionally, one new type was identified in this study: action dysphemisms 14 instances, indicating an expansion of dysphemism types within the context of comedy podcasts. In terms of function, three functions of dysphemism were identified: speaking about others in a derogatory manner 152 instances, expressing disagreement 31 instances, and expressing annoyance 78 instances. Additionally, one additional function was identified: expressing admiration or joy 20 instances, which demonstrates an expansion of the functions of dysphemism.